Strategies to Increase Teacher Commitment: A Study of The Influence of Emotional and Intellectual Intelligence with The Mediation of Job Satisfaction - Lailatul Fitriyah Lailatul; Rahmat Agus Santoso; Eva Desembrianita (South Sulawesi Education Development (SSED), 2024)
Education is a conscious effort that is deliberately planned to achieve a predetermined goal. Education really determines the progress and quality of a nation, therefore the potential of teachers as a component of human resources needs to be developed so that they can carry out their functions optimally. This research was conducted to find out what influences teachers' affective commitment. The research aims to analyze the influence of emotional intelligence and intellectual intelligence on teachers' affective commitment with job satisfaction as a mediating variable in MTs. Bungah Gresik, The type of research used in this research is quantitative causality research. The population and sample in this study were MTs teachers. Bungah Gresik, totaling 106 teachers.The results of the research show that emotional intelligence has a significant positive effect on affective commitment with a t-statistic value of 3.248 and a p-value of 0.001, intellectual intelligence has a significant positive effect on affective commitment with a t-statistic value of 3.917 and a p-value of 0.000, emotional intelligence has a significant positive effect on job satisfaction with a t-statistic value of 5.214 and a p-value of 0.000, intellectual intelligence has a significant positive effect on job satisfaction with a t-statistic value of 7.087 and a p-value of 0.000, job satisfaction has a significant positive effect on affective commitment, emotional intelligence has a significant positive effect on commitment affective through job satisfaction with a t-statistic value of 3.344 and p-value 0.001, and intellectual intelligence has a significant positive effect on affective commitment through job satisfaction with a t-statistic value of 3.025 and p-value 0.002. And the mediating variable job satisfaction cannot mediate between emotional intelligence and intellectual intelligence on the affective commitment of teachers at MTs. Assa'adah Bungah with a t-statistic value of 2.737 and a p-value of 0.006.From the results of the research, it is hoped that MTs Bunga Gresik teachers will increase cooperation between teachers and be sensitive to the surrounding environment in order to help harmonize the existing organizational structure. Apart from that, further research is expected to use other mediating variables such as work motivation due to job satisfaction.